Electricity from renewable resources : status, prospects and impediments - National Research Council (U.S.). Panel on Electricity from Renewable Resources; National Academy of Sciences (U.S.); National Academy of Engineering; National Academies Press (U.S.) (Washington, D.C. : National Academies Press, 2010)
"A component in the America's Energy Future study, Electricity from Renewable Resources examines the technical potential for electric power generation with alternative sources such as wind, solar-photovoltaic, geothermal, solar-thermal, hydroelectric, and other renewable sources. The book focuses on those renewable sources that show the most promise for initial commercial deployment within 10 years and will lead to a substantial impact on the U.S. energy system. A quantitative characterization of technologies, this book lays out expectations of costs, performance, and impacts, as well as barriers and research and development needs. In addition to a principal focus on renewable energy technologies for power generation, the book addresses the challenges of incorporating such technologies into the power grid, as well as potential improvements in the national electricity grid that could enable better and more extensive utilization of wind, solar-thermal, solar photovoltaics, and other renewable technologies."--Publisher's description.
Introduction -- Resource base -- Renewable electricity generation technologies -- Economics of renewable electricity -- Environmental impacts of renewable electricity generation -- Deployment of renewable electric energy -- Scenarios.
Includes bibliographical references.
Keywords: Renewable energy sources -- United States